The Implementation of Development Policy for The New School Unit of SMP Negeri 20 Singkawang - Asep Wahyudin; Maswardi M. Amin; Sukmawati Sukmawati (STKIP Singkawang, 2018)
The purpose of this study was to explore, analyze and reveal the process of implementing local government policies in the effort to fulfill the infrastructure of the New School Unit of Junior High School in Singkawang City. The approach used in this study is qualitative with the type of descriptive research in the form of case studies. Planning the Planning Process of the Development Policy Implementation of the New School Unit of SMP Negeri 20 Singkawang is carried out by the agency and the school. The agency makes technical instructions for implementing new student admissions that refer to ministerial regulations. The involvement of various parties and the availability of supporting data is needed in the planning process of Singkawang Junior High School New School Unit Development. The results obtained from this study are (1) Planning of the Planning Process of the Development Policy Implementation of the NewSchool Unit of SMP Negeri 20 Singkawang carried out by the agency and the school; (2) The Implementation of Development Policy for the New School Unit of SMP Negeri 20 Singkawang is carried out in accordance with the existing technical guidelines; (3) The role of stakeholders in the implementation of local government policies in the effort to fulfill the infrastructure of the SMP Negeri 20 Singkawang New School Unit in Singkawang City, in accordance with the respective authorities and abilities; (4) Evaluation is carried out to see which stages or parts still need improvement.